Analysis of Influence of the Cable Lay Equipment on the Main Dimensions of Subsea Construction Vessel - Egorov, A.G.; Goyushov, R.G.; Abdullayev, О.М. (Herald of Azerbaijan Engineering Academy, 2025)
The study proposes to determine and justify the required main dimension of the subsea construction vessel (SCV) using the database method. Using the database of cable-laying vessels, dependencies were developed and mathematically described that reflect the influence of the parameters of the cable-laying equipment on the main dimension of the vessel. Using the dependencies, the previously developed nomogram for determining the main dimension of the (SCV) was supplemented. Taking into account the parameters of cable-laying operations in the Caspian Sea and relying on the developed dependencies and nomogram, the necessary special (SCV) were created to perform work on laying and repairing underwater cable lines.